A SIMPLE RUN-UP CALCULATION OF TSUNAMI KRAKATAU 1883 FOR THE EVALUATION OF NCICD SEAWALL DESIGN - Eduardo Meyrianso Simanjuntak; Juventus Welly Radianta Ginting; Ida Ayu Irawati Diah Ratna Putra (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2020)
NCICD (National Capital Integrated Coastal Development) Seawall is designed mainly to prevent coastal flooding due to sea level rise and land subsidence in North Jakarta. However, the seawall is not designed to countermeasure a tsunami impact. The purpose of this research is to calculate tsunami impact in term of run-up in five strategic points such as Pelabuhan Muara Angke, Pelabuhan Nizam Zachman, Pantai Ancol, Pelabuhan Tanjung Priok dan Pantai Marunda. In this research, the seawall is evaluated for the worst-case tsunami scenario within the order of Tsunami Krakatau 1883. The source of tsunami is the initial condition from Maeno and Imamura (2011). The propagation from source to coastal area is conducted using SWASH model. SWASH 2D model shows a good agreement with observation data. Compared to Maeno and Imamura’s model, the numerical model shows a better agreement. The verified model is then extracted and the time series is used as an input for the 1D model to calculate the tsunami run-up. The model result shows that Tanjung Priok and Pantai Muranda are the most vulnerable point with tsunami run-up about 4 m. However, the current designed seawall with 4.8 m height is still sufficient to deal with this impact.